Leg preference and interlateral asymmetry of balance stability in soccer players - Teixeira, L. A.; de Oliveira, D. L.; Romano, R. G.; Correa, S. C. (Research Quarterly for Exercise and Sport, 2011)
To examine the effect of long lasting practice on pedal behavior in sport, we compared experienced adult soccer players and nonsoccer players on leg preference in motor tasks requiring general mobilization, soccer related mobilization, and body balance stabilization. We also evaluated performance asymmetry between the right and left legs in static and dynamic unipedal body balance, based on center of pressure displacement, and correlated that with leg preference in balance stabilization tasks. Results revealed (a) a distinct leg preference between mobilization and stabilization tasks, which were significantly different between players and nonplayers, (b) similar balance stability between the right and left legs, (c) greater stability of experienced players compared with nonplayers in static and dynamic balance, and (d) absence of a significant leg preference correlation with interlateral balance asymmetry. These results suggest an effect of extensive soccer skill practice on establishing leg preference for specific mobilization tasks and overall balance control.